Anti-angiotensin II type 1-receptor antibodies (AT1R-Ab) Induce a Specific Phenotype of Rejection Distinct from HLA antibody-Mediated Rejection. (July 2018) - Lefaucheur, Carmen; Viglietti, Denis; Aubert, Olivier; Philippe, Aurélie; Halloran, Philip; Loupy, Alexandre; Dragun, Duska
Abstract : Anti-angiotensin II type 1-receptor antibodies (AT1R-Ab) have been associated with kidney allograft rejection; however, their ability to induce a specific rejection phenotype, independent of the presence of donor-specific anti-HLA antibodies (HLA-DSAs), has not been defined. In a prospective cohort of 881 kidney recipients transplanted between 2007 and 2010, we performed systematic screening for AT1R-Ab using quantitative ELISA and HLA-DSAs using single antigen bead assay, together with concomitant allograft biopsy, at the time of any clinical event in the first-year post-transplantation and at 1 year after transplantation. The allograft rejection phenotype was assessed by histopathology, immunochemistry for C4d complement fraction, and allograft gene expression measurement using microarray. We identified 233/881 (26%) patients with post-transplant AT1R-Ab (>10 U/mL). Compared to AT1R-Ab negative patients, AT1R-Ab positive patients showed increased levels of glomerulitis (p=0.01), peritubular capillaritis (p=0.01), endarteritis (p=0.01), similar level of interstitial inflammation (p=0.66) and tubulitis (p=0.23), and similar prevalence of C4d deposition in capillaries (p=0.24) and transplant glomerulopathy (p=0.99). After adjusting for the detection of HLA-DSAs, AT1R-Ab were independently associated with glomerulitis (aOR=1.7, p=0.006), peritubular capillaritis (aOR=1.8, p=0.002) and intimal arteritis (aOR=2.1, p=0.01). Among patients with microcirculation inflammation (g+ptc>1) (N=154), patients with AT1R-Ab and without HLA-DSA (N=23) showed increased prevalence of intimal arteritis (39%) and decreased prevalence of C4d deposition in capillaries (17%) compared to patients without AT1R-Ab and with HLA-DSA (N=80, 13% and 51%, respectively), to patients with AT1R-Ab and with HLA-DSA (N=31, 16% and 55%, respectively), and to patients without AT1R-Ab and without HLA-DSA (N=20, 5% and 10%, respectively) (p<0.001 and p=0.01, respectively). Compared to patients without AT1R-Ab and with HLA-DSA, patients with AT1R-Ab and without HLA-DSA exhibited increased expression of endothelial cell associated transcripts in allograft, including MEOX2, MEOX1 and FOSB (FC=3.9, 3.0 and 2.7, respectively, p<0.001 for all). Histomolecular rejection phenotype in patients with AT1R-Ab and without HLA-DSA was distinct from that of patients without AT1R-Ab and with HLA-DSA in unsupervised clustering. AT1R-Ab are associated with a specific histo-molecular phenotype of kidney allograft rejection, characterized by microvascular and arterial inflammation, expression of endothelial cell associated transcripts and low prevalence of complement deposition in capillaries, independent of the presence of HLA-DSAs.